The Biology of Fall Army Worm (Spodopterafrugiperda. J. E. Smith) in Sudan - Nada Elsheikh M. Kona; Awad KhalafallaTaha; Mohammed E. E. Mahmoud; Abubaker Haroun Mohamed Adam (Journal of Agronomy Research, 2021)
The Fall armyworm (Spodoptera frugiperda) is considered among the economic important pests in Sudan. Therefore, it became necessary to study and understand its biology and find out the appropriate control measure (s). To achieve the above objective, experiments based on Randomized Complete Block Design (RCBD) were carried out during the period from September 2018 to August 2019, where the Fall armyworm (FAW) was reared in the laboratory and fed on a nutrient médium composed of Corn leaves. The results displayed the ranges of eggs laid by a female was 890–1169. The egg incubation period ranged between 3-13 days. The larval duration ranged between (13-50) days and the pupal duration was between (7-20) days under a temperature of 21-300c and a Relative Humidity (RH) of 65 ± 5%. The longevity of the adults was 1-20 days, and the range of the full lifecycle was (24-100). However, six generations of FAW were obtained within one year. This study concludes that in Sudan FAW breeds continously throughtout the year and it recommends further studies on the biology and effective management of this invasive pest
Keywords: Annual generations